Acid-activated bentonite blended with sugarcane bagasse ash as low-cost adsorbents for removal of reactive red 198 dyes. Issue 2 (18th March 2022) - Adane, Teshale; Hailegiorgis, Sintayehu Mekuria; Alemayehu, Esayas
Abstract: The present research work investigated the removal efficiency of acid-activated bentonite blended with a sugarcane bagasse ash (SCBA) adsorbent for the removal of reactive red 198 (RR198) from a synthetic dye solution. The effect of the adsorption parameters of bentonite on SCBA blending ratio, dye solution pH, adsorption contact, adsorbent dosage, and initial dye concentration was investigated, and the parameters were optimized for maximum RR198 removal from the synthetic dye solution. At an optimum condition of 1:1 bentonite to the SCBA blending ratio, a solution pH of 2, 3.7 g/L of adsorbent dosage, and 15 mg/L of initial dye concentration 150 min of adsorption time, the properties of adsorbents such as adsorbent specific surface area, crystalline phase structure, functional groups, and surface morphologies of the adsorbents were investigated. At optimum conditions, 97% RR198 removal efficiency of the adsorbent was achieved. In order to determine adsorption kinetics and isotherm models, different adsorption models were employed. It was observed that the adsorption of the RR198 dye into the acid-activated bentonite blended with the SCBA adsorbent was represented well by the Langmuir isotherm model and the adsorption kinetics order was found to be the pseudo-second order. HIGHLIGHTS: Regenerable and low-cost adsorbents. Removal of reactive dye using blended inorganic and organic adsorbents. Principle of waste to wealth. Improving the quality of industrial wastewater effluents. Graphical Abstract